Increased Levels of Nerve Growth Factor Indicating Brain Injury In Mice Model - Prastiya Indra Gunawan; Riza Noviandi; Sunny Mariana Samosir (Universitas Wijaya Kusuma Surabaya, 2022)
Hypoxic-ischemic encephalopathy (HIE) brain injury is one of the leading causes of death and disability worldwide. Nerve growth factor (NGF) is a neurotrophin that plays an important role in the natural repair and regeneration of nerves, but the previous study regarding NGF level after brain injury is still scant. This study aims to determine NGF levels in male Wistar rat models that received right Common Carotid Artery (CCA) occlusion. This study used an experimental and control design conducted in July-August 2021 at the Stem Cell Research and Development Center, Universitas Airlangga. The right CCA occlusion was performed on the Wistar mouse model in the treatment group, then placed in a hypoxic chamber and reperfusion after 60 minutes. Observations of neurology scores were carried out in the first 24 hours. After 2x24 hours the animal was sacrificed for serum NGF level measurement using the ELISA method. Statistical analysis using t-test for independent sample. A total of 16 male rats participated in the study. Eight rats in the treatment group were put into hemiparesis at different levels according to observations of neurological scores. Statistically meaningful differences in NGF levels were found in the treatment group compared to controls (P<0.05). Average NGF levels in the treatment group were higher than in the controls. NGF levels in mice with HIE were higher than the control group, which indicates the body's natural mechanism for neuron protection following ischemic hypoxic events.